The Discoloration of Heat Cured Resin Acrylic Base After Immersed in Disinfectant Solution - Sintha - Nugrahini (Maranatha Christian University, 2020)
Acrylic resin dentures are a type of denture that is often used. At present the use of disinfectants to clean dentures from microorganisms, such as sodium hypochlorite and green betle leaves. Sodium hypochlorite contains chlorine, and green betle leaf extract contains tannins that containable to provide color changes in artificial teeth. The purpose of this study was to study the change in color on the hot polymerization acrylic plate after soaking with sodium hypochlorite solution and green betle leaf extract (Piper betle Linn). This study was a pre-post test control group design, the sample was heat-cured resin acrylic base plate and divided into 3 treatment groups: a group immersed in sodium hypochlorite, extract of green betel leaf and control group with aquades. The discoloration measurement was using Spectrophotometer. The sample was immersed for 15 days. Data were analyzed by paired T-test, followed by One way Anova and LSD. The results showed that there were significant color changes in the 2 treatment groups, while the control group was not significant. The mean of discoloration after immersion with Sodium Hypochlorite was 0.668 + 0.018, green betle leaf extract 30% was 0.625 + 0.024, and aquades was 0.534 + 0.0224. Color changes on heat-cured resin acrylic base plate occur by the presence of chlorine in sodium hypochlorite and tannin contained in the green betel leaf extract. This research concluded that immersion of heat-cured resin acrylic plate in sodium hypochlorite solution and 30% betle leaf extract may cause discoloration.